Effective Communication Strategies for Marketing Halal Products in Taiwan Using the Best Worst Method (BWM) - Muhammad Ghalih; Chia-Hua Chang (Universitas Lambung Mangkurat, 2024)
This article investigates effective communication strategies for marketing halal products in Taiwan, leveraging the Best Worst Method (BWM) to prioritize these strategies systematically. Given the increasing demand for halal products among local and international Muslim communities, it is imperative for businesses to adopt culturally sensitive and efficient marketing approaches. The BWM is utilized to evaluate and rank key strategies, including cultural sensitivity and respect, digital marketing, community engagement, and collaborations and partnerships. Implementing these prioritized strategies allows businesses to effectively connect with the Muslim community in Taiwan, enhancing their ability to promote halal products successfully and build enduring customer relationships.